Intangible capital and firms productivity - Emanuela Marrocu; Raffaele Paci; Marco Pontis (European Regional Science Association (ERSA), 2010)
Firms competitive strategy in industrialised countries is increasingly based on activities such as the inventions of new processes and products, the improvements of the employees skill, the creation of a reputation for company's products. All these actions are intended to increase firms economic performances and are labelled as "intangible capital". The aim of this paper is to evaluate the role of intangible capital on firms productivity in addition to the well-known one played by traditional inputs. Firms productivity may also depend on the socio-economic conditions of the region where the firm is located. Therefore, we also control for the physical endowments of the region (public capital, infrastructures) as well as for several types of intangible assets specific to the region (human, technological and social capital) that yield positive externalities to the localised firms. In our empirical application we employ a large panel of European companies over the period 2002-2006 belonging to 116 regions of six countries. The estimation results - robust to various ways of disaggregating the sample data (by country, macro-sector and firms dimension) and to different econometric methodologies (2SLS, Olley-Pakes, Levinsohn-Petrin) - show the positive influence of the internal intangible capital on firms productivity levels and also the crucial role played by the intangible assets at the regional level. These results remark the importance of policies designed to stimulate the accumulation of intangible capital stocks internal to the firms through appropriate fiscal policies and to create a favourable external environment based on high endowments of human, social and technological capital.
Keywords: D24; O30; C33; R10; 330; firms productivity; intangible capital; knowledge externalities; Europe